Investigating the viability of motoric task performance as a clinical biomarker in Huntington’s and Parkinson’s disease - Jayaraj, MS (2014)
Evaluating hand tapping as a clinical biomarker in Parkinson and Huntington’s diseases, using an Android device was the objective of the study. A novel hand -tapping tool using an Android OS was developed over a year, which included 5 tapping tasks. The application was meant for installation on Samsung Galaxy 7” tablet devices. The tasks included finger tapping; metronome based tapping, simple and choice reaction time and was used to study a cross section of 45 controls of three different age groups, from 20-30 years, 35 -45 years and 65-80 years. Age and gender matched controls to Parkinson’s subjects (n=21) and Huntington’s disease patients (n=17) were assessed using the same tapping tasks. Baseline values for various tapping measures such as tapping rate, inter-tap interval, force, pro-tap (simple) reaction time, anti-tap(choice) reaction time were obtained. The study reported a significant difference between 20-30 year olds and 65-80 year olds in tapping rates and inter-tap-interval of the double target tapping task. Displacement, pro-tap time and anti-tap times were lower in 20-30s and 35-45 year olds compared to the 65-80s group. PD patients showed markedly lower values and were significantly different from controls in tapping rates, displacement of single target tapping, tapping rates and inter-tap-interval of double target tapping, pro-tap and anti-tap times and their standard deviation. HD patients had significantly lower values in inter-tap-intervals, displacement of single finger tapping, tapping rates, inter-tap interval and displacement of double target tapping, pro-tap and anti-tap reaction times. In conclusion, the study enabled us to identify tapping parameters and reaction time tests which have the potential to differentiate between Parkinson’s and Huntington’s patients with controls, therefore making motoric task performance a potentially viable clinical biomarker in HD and PD.